KAJIAN STUDI GEOTEKNIK KLASIFIKASI TANAH PERMUKAAN UNTUK PERENCANAAN PEMBANGUNAN DIKAWASAN UNIVERSITAS SAMUDRA - Farhan, Muhammad; Novita Lydia, Ellida; Fajri, Haikal (Universitas Muhammadiyah Palembang, 2024)
Soil classification is a science that aims to study ways to differentiate soil properties and divide soil into classes based on general characteristics. The aim of this research is to determine the physical properties of the land surface and determine the classification of surface land in the Samudra University area to be mapped based on soil type using ArcGis. 38 undisturbed soil samples were taken using a hand drill and 38 soil samples were tested in the laboratory to determine the physical properties of the soil and to map research results for surface soil types using Arcgis with the kriging interpolation method. From the test results, the lowest water content was at point 35 with a value of 4 55% and the highest was at point 5 with a value of 62 64%. The lowest liquid limit was at point 1 with a value of 15 65% and the highest was at point 13 with a value of 47 99% and the lowest plasticity index was at point 5 with a value of 5 70% and the highest at point 3 with a value of 26 93% while the lowest filter analysis was at points 10 and 12 with a value of 0% and the highest was at point 5 with a value of 40 74%. From the research results, it was concluded that the soil types in the Ocean University area received 7 classification groups based on AASHTO with the most dominant group being group A.2-6 with 19 points.